Catchment‐scale distribution, abundance, habitat use, and movements of European eel (Anguilla anguilla L.) in a small UK river: Implications for conservation management. Issue 5 (5th March 2022) - Harwood, Andrew J.P.; Perrow, Martin R.; Sayer, Carl D.; Piper, Adam T.; Berridge, Richard J.; Patmore, Ian R.; Emson, Dave; Cooper, George
Abstract: Effective conservation management of the Critically Endangered European eel ( Anguilla anguilla ) is hindered by incomplete understanding of distribution, abundance, and habitat requirements at the catchment scale. All habitats available to eels within a small, highly regulated river catchment, representative of many used across the species' range, were sampled using several methods (including point abundance sample electric fishing and fyke nets) and supplemented by individual telemetry to investigate movements. Eels were found throughout the catchment (59% of n = 131 sites) from the coastal marshes to the headwaters, although the probability of presence declined with distance from the estuary. The lack of a clear relationship with perceived barriers may illustrate a mismatch with the reality experienced by eels, as telemetry identified connectivity across obstacles between paludal habitat and estuary, and detected escapement of mature silver eels from both lotic and lacustrine habitat. Different size/age classes occurred in different parts of the catchment, partly linked to different habitat associations, with coastal paludal habitat supporting >50% of the catchment population and especially smaller (possibly male dominated) yellow eels. Recently recruited elvers were most abundant in the lower reaches of lotic habitat. The largest (probably female) eels were concentrated in lacustrine sites, especially at the 'end‐of‐the‐line' in the headwaters. Experiences here suggest that conservation management for eels in small catchments is best focused on: (i) improving connectivity and assisting migration of elvers across 'problem' barriers that cannot be removed or modified, (ii) river restoration and rewilding, especially measures that increase instream woody material to provide refuge habitat and, (iii) enhancement or creation (where necessary) of suitable lacustrine habitat to benefit large females in particular. Such action across numerous small river catchments may ultimately help support the recovery of eel stocks.